New Estimation of Antibiotic Resistance Genes in Sediment Along the Haihe River and Bohai Bay in China: A Comparison Between Single and Successive DNA Extraction Methods - Wu, Chao; Zhang, Guicheng; Xu, Wenzhe; Jian, Shan; Peng, Liyin; Jia, Dai; Sun, Jun (Frontiers in Microbiology, 2021)
Sediment is always thought to be a vital reservoir for antibiotic resistance genes (ARGs). Often, studies describing and comparing ARGs and their potential hosts in sediment are based on single DNA extractions. Till now, however, none study has been conducted to access the influence of DNA extraction efficiency on ARGs in sediment. To determine whether ARGs abundance are underestimated, we performed five successive extractions by a widely used commercial kit in ten sediment samples collected from the Haihe River and the Bohai Sea. Our results showed that accumulated DNA yields after five extractions were 1.8-3.1 times than that by single DNA extractions. High throughput sequencing results showed that incomplete DNA could generate PCR bias and skew community structure characterization in sediment. The relative abundance of some pathogenic bacterium, such as Enterobacteriales, Lactobacillales and Streptomycetales, have significant difference between single and successive DNA extraction samples. In addition, real-time fluorescent quantitative PCR (qPCR) presented that ARGs, intI1, and 16S rRNA gene abundance strongly increased with the increasing of extraction steps. Among measured ARGs, sulfonamide resistant genes and multidrug resistant genes were dominant subtypes in the study region. Nevertheless, different subtypes of ARGs didn’t response equally to the additional extraction steps, some of them continued to have linear growth trends and some of them tended to leveled off. Additionally, more correlations between ARGs and bacterial communities were observed in the successive DNA extraction samples than that in the single DNA extraction samples. It is suggested that 3-4 additional extraction steps are greatly required in the future study when extract DNA from sediment samples. Taken together, the findings from the present study will improve our knowledge of ARGs and their potential hosts in sediment around the Bohai Bay region, and have referential value for similar study how to accurately evaluate ARGs in sediment.